The Landscape of Financial Performances of Sharia Business Unit in Indonesia - Ahmad Abbas; Nengsi Warna Sari (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2022)
The condition of financial performance is very important to evaluate because every bank will always face financial problems. Sharia Business Unit is one of the Islamic banks that is rarely highlighted for its financial performance because it is still attached to its parent company, namely conventional banks. The purpose of this study is to describe the financial performance of sharia business units. This type of research is descriptive quantitative. The sample of this study is the Sharia Business Unit in Indonesia. Data obtained from the Financial Services Authority during 2016-2018. Ratio analysis is used to obtain an overview of the data. The results of this study show that the financial performance of the Sharia Business Unit is considered good.